Queering Child and Youth Care - Vachon, Wolfgang (International Journal of Child, Youth and Family Studies, 2020)
Building on queer theory, on formative and current discourses of child and youth care (CYC), and on feminist and other ethics of care theorizing, this paper applies queer analytics to CYC by considering how desire, identity, sexuality, theory, and politics may be taken up within CYC.